Managing Small Business : an entreprenuerial emphasis - Moore, Carlos W.; Petty, William J.; Palich, Leslie E.; Longenecker, Justin G. (Australia: South Western: Cengage Learning, 2010)
The textbook is a guide to managing small business.
Includes Index.
rua 06/01/14
Loans
Keywords: Small business --Management.